2013
DOI: 10.3109/02713683.2012.760741
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Responses Induced by Pharmacologic Vitreolysis and/or Long-term Hyperoxia Treatment in Rat Lenses

Abstract: Purpose The aim of the study was to investigate the protective effects of intact vitreous gel on the lens after pharmacologic vitreolysis and hyperoxia exposure in rats in vivo. Methods Eyes of Sprague-Dawley rats were induced to posterior vitreous detachment (PVD) by pharmacologic vitreolysis, and the rats with and without PVD were treated with hyperoxia 3 h per day for 5 months. Lens transparency was monitored by a slit-lamp biomicroscope. A series of biochemical measurements were made in extracts of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Sebag et al 48 showed enhanced nanosphere diffusion in the vitreous after treatment with microplasmin (a shorter version of plasmin with the same proteolytic domain; now called ocriplasmin). Moreover, increased oxygen content in the vitreous body and in the lens after plasmin or microplasmin treatment has been reported by a number of investigators, [49][50][51] Enzyme-Induced Vitreous Remodeling IOVS j December 2014 j Vol. 55 j No.…”
Section: Discussionmentioning
confidence: 93%
“…Sebag et al 48 showed enhanced nanosphere diffusion in the vitreous after treatment with microplasmin (a shorter version of plasmin with the same proteolytic domain; now called ocriplasmin). Moreover, increased oxygen content in the vitreous body and in the lens after plasmin or microplasmin treatment has been reported by a number of investigators, [49][50][51] Enzyme-Induced Vitreous Remodeling IOVS j December 2014 j Vol. 55 j No.…”
Section: Discussionmentioning
confidence: 93%
“…Similar treatment in rats increased oxygen levels in the lens [12]. When rats were exposed to HBO, vitreolysis lowered ascorbate levels in the vitreous and aqueous humors, decreased levels of protective enzymes in the lens, and increased levels of Glutathione (GSH)-protein mixed disulfides in the lens compared to animals with the vitreous intact [13].…”
Section: Vitreous Degeneration and Nuclear Sclerotic Cataractmentioning
confidence: 95%
“…While one could argue that nothing new was to be expected concerning the protective role of GSH in the lens, our interest in GSH homeostasis in the lens was rekindled with the unexpected finding that lenticular GSH levels were not completely suppressed in the LEGSKO mouse in spite of complete absence of γ-glutamylcysteine ligase(Fan et al, 2012). This issue, which is the subject of intense investigation in our laboratory, is closely linked to lenticular ascorbate metabolism and cataractogenesis and the work of David Beebe who has pioneered the importance of the vitreous as a source of oxidative stress to the lens(Beebe et al, 2014; Holekamp et al, 2005; Li et al, 2013b; Shui et al, 2009). These paradigm shifting studies inspired us to study lens biology in connection not only to the aqueous humor but also to the vitreous humor.…”
Section: Introductionmentioning
confidence: 99%